Criminal offences and civil wrongs by or against migrant workers - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
Despite the existence of labour legislations, migrant workers, in certain sectors, are still subjected to physical, verbal or psychological abuse with little or no consideration of their well-being. For example, poor and unsafe working standards, excessive working hours, non-payment or lower payment of wages, forced labour, child labour and sexual exploitation, among others are still being reported. An employer who physically abuses or maltreats their migrant workers may be charged in court pursuant to the Penal Code (Act 574) (Revised 1997). The Penal Code is the principal statute in Malaysia relating to criminal offences. If he is found guilty, an employer may be subjected to severe penalties such as imprisonment, fine and/or whipping.Likewise, a migrant worker who takes the law into his own hand by inflicting injury or harm on the employer or their properties, may be dealt with in the court and if found guilty, he may be sentenced in accordance with the severity of the offence committed.